The process of preparation and analysis of calcareous nannofossil sample, and application for marine sediments of Soc Trang province - Nhung, Nguyen Thi Hong; Thuy, Nguyen Thi; Hien, Nguyen Viet; Manh, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2020)
Calcareous nannofossils are very small microfossils composed of calcium carbonate. They are very good biostratigraphic markers within marine sediments by covering the Jurassic to present. The standard preparation of a sample for nannofossil analysis requires the collection of the largest quantity and the best fossils. Sample preparation accords to the following steps: i. Pounding sample; ii. Eliminating organic matter; iii. Washing sample; iv. Filter sample through the sieve; v. Eliminating clay; vi. Drying sample in an incubator; vii. Packing sample. Sample analysis accords to the following steps: i. Preparation of smear - slide; ii. Observation of morphology; iii. Determination; iv. Taking photo; v. Evaluating overall preservation and abundance of fossils; vi. Making analysis result sheet. This process is applied to study calcareous nannofossils within marine sediments in Soc Trang province. It makes much clear to understand middle Pleistocene-early Holocene ecosystem of calcareous nannofossil. In conclusion, this assemblage belongs to NN21 zone by the present of Emiliania huxleyi and Gephyrocapsa oceanica.